Prevalence of burnout in medical students in China: A meta-analysis of observational studies. Issue 26 (2nd July 2021) - Li, You; Cao, Liang; Mo, Chunbao; Tan, Dechan; Mai, Tingyu; Zhang, Zhiyong
Abstract : Abstract: This meta-analysis aimed to estimate the prevalence of burnout among medical students in China. A systematic search from the following electronic databases: China National Knowledge Infrastructure, Wangfang database, VIP database, Chinese biomedical literature database, PubMed, Embase, Web of Science, and Google Scholar was independently conducted by 2 reviewers from inception to September 2019. The data were analyzed using stata software Version 11. Heterogeneity was assessed using I 2 tests, and publication bias was evaluated using funnel plots and Egger's test. The source of heterogeneity among subgroups was determined by subgroup analysis of different parameters. A total of 48 articles with a sample size of 29, 020 met the inclusion criteria. The aggregate prevalence of learning burnout was 45.9% (95% confidence interval [CI] = 38.1%–53.8%). The prevalence rate of high emotional exhaustion was 37.5% (95% CI: 21.4%–53.7%). The percentage was 44.0% (95% CI: 29.2%–58.8%) for low personal accomplishment. The prevalence rate was 36.0% (95% CI: 23.0%–48.9%) in depersonalization dimension. In the subgroup analysis by specialty, the prevalence of burnout was 30.3% (95% CI: 28.6%–32.0%) for clinical medicine and 43.8% (95% CI: 41.8%–45.8%) for other medical specialties. The total prevalence of burnout between men and women was 46.4% (95% CI: 44.8%–47.9%) and 46.6% (95% CI: 45.5%–47.6%), respectively. The prevalence of burnout with Rong Lian's scale was 43.7% (42.1%–45.2%), and that with the other scales was 51.4% (50.4%–52.4%). The prevalence rates were 62.9% (61.3%–64.6%), 58.7% (56.3%–61.1%), 46.5% (42.9%–50.2%), and 56.0% (51.6%–60.4%) from Grades 1 to 4, respectively. There was a statistically significant difference among the different grades ( P = .000). Our findings suggest a high prevalence of burnout among medical students. Society, universities, and families should take appropriate measures and allot more care to prevent burnout among medical students. Abstract : Supplemental Digital Content is available in the text